Produção de um material didático pedagógico de apoio ao professor visitante do Show de Física - Ferrazo, André Kyoshi Fujii [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Teaching can take place in different educational environments. Schools are an example of a formal teaching environment, governed by welldefined norms, with the content worked in a hierarchical and segmented way. In this bias, the Science Museums are spaces of informal teaching, given the playful and relaxed character in which the concepts are approached in these institutions, presenting them with demonstrations in an informality atmosphere. However, it is clear that both institutions can potentially contribute to the learning of the students. The Physics show is an interactive Science Museum that promotes the visiting of the public to experience a series of phenomena in the field of physics in an informal environment. In this work, it is presented the elaboration of a pedagogical didactic material to support the visiting professor of the show. This material is composed by videos of some of the demonstrations that take place in the Physics Show, a theoretical reference material at the university level for the teacher and a series of activities proposed to be worked in the classroom. These activities were selected in order to contemplate the competencies stipulated by the National Curricular Parameters in the area of Natural Sciences, Mathematics and their Technologies. In this aspect, it can be stated that certain competencies were privileged in the elaboration of the material, highlighting which area of Physics is favored in the presentations of the Show

O ensino pode se dar em diferentes ambientes educacionais. Como exemplo de um ambiente de ensino formal têm-se as escolas, regidas por normas bem definidas, com o conteúdo trabalhado de maneira hierarquizado e segmentado. Neste viés, os Museus de Ciência são espaços de ensino informal, dado o caráter lúdico e descontraído em que os conceitos são abordados nestas instituições, apresentando-os com ar de informalidade nas demonstrações. No entanto é evidente que ambas as instituições podem contribuir potencialmente para a aprendizagem dos estudantes. O show de Física é um Museu de Ciência interativo que promove ao público visitante vivenciar uma série de fenômenos na área da física num ambiente informal. Neste trabalho é apresentada a elaboração de um material didático pedagógico de apoio ao professor visitante do Show. Esse material é composto por vídeos de algumas das demonstrações que ocorrem no Show de Física, um material de referencial teórico a nível superior para o professor e uma série de atividades propostas a serem trabalhadas em sala de aula. Estas atividades foram selecionadas de maneira a contemplar as competências estipuladas pelos Parâmetros Curriculares Nacionais na área de Ciências da Natureza, Matemática e suas Tecnologias. Neste aspecto, pode-se constatar que determinadas competências foram privilegiadas na elaboração do material, evidenciando qual a área da física é favorecida nas apresentações do Show
Keywords: Material didático; Ensino - Meios auxiliares; Física - Estudo e ensino